SOLVING PROBLEM METHOD AS IMPROVEMENT OF MOTIVATION AND SKILLS IN VOCATIONAL EDUCATION - Suyitno Suyitno (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to determine the increase in motivation and mastery of the practice of maintaining a 4 speed deer manual transmission system using the problem solving method. This research is a Classroom Action Research (CAR). The subjects of this study were 34 students of class XI TKR-7. The study was conducted in two cycles and each cycle consisted of five meetings, the first meeting in cycle I and cycle II was practical learning and the second to fifth meeting at the end of the cycle was a practice test. Data collection methods in this study used questionnaires, observations, tests, and documentation. The aspects studied include student motivation and student skills outcomes. The action given by the teacher is practical learning using problem solving practice methods . The steps undertaken in this study are compiling practical learning material in the form of job sheets practice, then the job sheet is distributed to the learning teams to work on, then after completing the next step the practice evaluation is carried out. Data were analyzed using descriptive statistics . The results showed an increase in student motivation and skills in vocational subjects to improve the 4 speed deer manual transmission system . This is indicated by: (1) the percentage of students' learning motivation when learning practices in the first cycle reached 85.60%, with moderate criteria, in the second cycle increased to 76.19%, with high criteria. (2) the average value of student learning outcomes in the first cycle was 79.48 with good criteria, in the second cycle increased to 83.06, with very good criteria. (3) the classical learning completeness of students in cycle 1 was 82.36%, with high criteria, in cycle II it increased to 94.1 2 % with very high criteria.